Cocoa (Chocolate Bean) Growing in the Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi; Gene Joyner (EDIS)
Revised! HS-1057, an 8-page fact sheet by Jonathan H. Crane, Carlos F. Balerdi, and Gene Joyner, provides homeowners with a basic reference for growing cocoa (chocolate bean) in the home landscape. Tables include suggested cultural practices by month, fertilizer recommendations and nutritional values. Published by the UF Department of Horticultural Sciences, October 2006.